2019
DOI: 10.2147/ott.s220462
|View full text |Cite
|
Sign up to set email alerts
|

<p>FGFR1 Induces Acquired Resistance Against Gefitinib By Activating AKT/mTOR Pathway In NSCLC</p>

Abstract: ObjectiveAs an epidermal growth factor, receptor-tyrosine kinase inhibitor (EGFR-TKI), gefitinib demonstrates a good therapeutic effect in patients with EGFR-mutant non-small-cell lung cancer (NSCLC). However, an overwhelming majority of these patients inevitably develop resistance against gefitinib. Unfortunately, the mechanism underlying this phenomenon is still not fully understood. Here we aim to reveal the mechanism of gefitinib resistance in NSCLC induced by FGFR1.Materials and methodsWe used high-throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…A recent study reported that HAX1 prevents glioblastoma cells from apoptosis through the Akt1 pathway, 15 and it has also been reported that the AKT/mTOR signal pathway plays an important role in NSCLC. AKT/mTOR signal pathway induces gefitinib‐resistant of NSCLC 19 . FAM83D has been reported to improve epithelial‐mesenchymal transition, invasion and cisplatin resistance through activating the AKT/mTOR pathway in NSCLC 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that HAX1 prevents glioblastoma cells from apoptosis through the Akt1 pathway, 15 and it has also been reported that the AKT/mTOR signal pathway plays an important role in NSCLC. AKT/mTOR signal pathway induces gefitinib‐resistant of NSCLC 19 . FAM83D has been reported to improve epithelial‐mesenchymal transition, invasion and cisplatin resistance through activating the AKT/mTOR pathway in NSCLC 20 .…”
Section: Resultsmentioning
confidence: 99%
“…AKT/mTOR signal pathway induces gefitinib-resistant of NSCLC. 19 FAM83D has been reported to improve epithelialmesenchymal transition, invasion and cisplatin resistance through activating the AKT/mTOR pathway in NSCLC. 20 The oncogene IARS2 promotes the occurrence of NSCLC by activating the AKT/MTOR pathway.…”
Section: Silencing Of Hax1 Reduces Invasion and Epithelial-mesenchymamentioning
confidence: 99%
“… 17 Besides, the expression of FGFR1 in NSCLC is significantly increased and high expression of FGFR1 implies an unfavorable prognosis of NSCLC patients; knockdown of FGFR1 sensitizes PC9 cells to gefitinib. 18 FGFR1 is proved to activate ERK signaling pathway, thereupon up-regulating expression of SOX2 and promoting the proliferation and migration of NSCLC cells. 19 Unfortunately, although the role of FGFR1 in NSCLC progression is confirmed and its inhibitors are designed to treat NSCLC, most of the studies are still at preclinical stage and the application of FGFR1 inhibitors in the clinical treatment of NSCLC is still facing great challenges.…”
Section: Discussionmentioning
confidence: 99%
“…17 Besides, the expression of FGFR1 in NSCLC is significantly increased and high expression of FGFR1 implies an unfavorable prognosis of NSCLC patients; knockdown of FGFR1 sensitizes PC9 cells to gefitinib. 18 FGFR1 is proved to activate ERK signaling pathway, thereupon up-regulating expression…”
Section: Discussionmentioning
confidence: 99%
“…The H-score system was used to assess the expression of target proteins, and the formula for the H-score is as follows: Histoscore = Σ (I × Pi), where I = intensity of staining and Pi = percentage of stained tumor cells [28]. MDA-MB-231 cells were seed on the dish with a density of about 30% and treated with 400 nM Mith A for 24 h. Immuno uorescence (ICC) was performed as described in our previous study [29].…”
Section: Transwell Migration Assaymentioning
confidence: 99%